A field study on the acoustic environment of special-needs education classrooms. Issue 4 (December 2019) - Ueno, Kanako; Noguchi, Saki; Takahashi, Hidetoshi
A child with a developmental disability, such as autism spectrum disorder, has a high possibility of having atypical sensorial characteristics. Indeed, children with autism spectrum disorder often face great difficulties while listening to teachers' instructions in noisy environments. Moreover, since some of their hearing is highly sensitive, specific or loud sounds may induce problematic behaviors. It is necessary to determine the acoustic requirements of a classroom by considering the atypical hearing properties of such children. In this study, we investigated the acoustic problems of schoolrooms for special-needs education and the methods to improve their sound environment. First, a questionnaire survey was conducted on the supervising teachers of the special-needs education class, and the children's disorders, hearing properties, and problems caused by the acoustic environment were examined. Simultaneously, an observational survey of the school was performed and acoustic problems were overviewed. Second, as a means to find a method to improve the problems caused by sound, a small calming space was constructed with metal frames surrounded by sound-absorbing material. It was experimentally placed in a classroom so that children could take refuge in the quiet environment. The effectiveness of the space was investigated by an observational survey of the classroom and an interview survey of the teachers.